PENGGALIAN KEBUTUHAN MENGGUNAKAN METODE PERSONA PADA SISTEM PENILAIAN LMS - Muhammad Imam (Universitas Madura, 2021)
The development of a software is very necessary to understand the users/users of the system. The aspect of user convenience in using the system is a very important aspect so that the system that has been created is in accordance with the purpose of its manufacture and according to user needs. Persona is a technique of Human Computer Interaction by collecting information from users as a reference in understanding the needs of users. The purpose of this study is to apply the persona technique by adjusting the validation process to the user personas of our system users. The method used in this research is the Human Computer Interaction technique. User persona is used as a reference so that a system is made based on user needs so that the purpose of making the system can be met. The result of this research is to use the user persona technique in the elicitation of needs which will facilitate understanding related to the development of a system.Keywords: Human Computer Interaction, Persona, Elicitation of Needs